NANOCOMPOSITE PROTECTIVE COVERINGS, PRECIPITABLE BY SEPARATED PLASMA - D. V. Kuis; S. D. Latushkina; I. M. Romanov; A. G. Zhizhchenko; N. A. Svidunovich; O. U. Piskunova; P. V. Rudak (Литьë и металлургия, 2011)
It is offered to use the complex approach to formation of the protective coatings, including deposition of coverings of multi-component structure with use of the separated plasma flows, in the present work.